Conscientização sobre o transtorno do desenvolvimento da linguagem no Brasil - Domingos, Talita Trigueiro (2022)
Development al Language Disorder (DLD) is not a new or rare condition, but internationally its public awareness is inferior to other conditions with lower incidence. In Brazil there is no documented study in the literature on the subject. To fill this gap, this dissertation aimed to investigate public awareness of Developmental Language Disorder in Brazil. For this, an observational, descriptive and cross-sectional study was developed, carried out through a questionnaire provided by the virtual platform Google Forms. This questionnaire corresponds to the translated version into Brazilian Portuguese of an instrument used internationally. Questions are divided into six sections, including demographic and social characteristics; awareness about conditions that compromise language development; the nature of DLD; speech-language therapy services; role of the family; and strategies to raise awareness about DLD, respectively. Data collection took place between July and November 2021, after approval by the Research Ethics Committee (opinion 4,801,877). A total of 320 valid responses were obtained, the results of which were divided into two studies. The first considered all the answers to describe a profile of this awareness in Brazil, while the second compared the topic between health (n=99) and educational (n=95) professionals. Based on their results, it was possible to verify that less than 40% of respondents had already heard of DLD. Even among health (38.4%) and educational (45.3%) professionals this index islow, pointing to the need forspecific actions to expand the dissemination of the DLD in Brazil.